Perancangan Sistem Persediaan Menggunakan Metode Extreme Programming - Temi Ardiansah (Jurnal Ilmiah Informatika dan Ilmu Komputer (JIMA-ILKOM), 2022)
PT ABC is a trading business engaged in selling goods to customers. Sales of goods include, among others, tires, spark plugs, 2-wheel and 4-wheel lubricants. The problem that exists in the inventory process is that making sales notes and invoices for delivery of goods is still done manually, namely by writing on notes and invoices for delivery of goods to be given to customers, thus slowing down staff performance in processing sales transactions. In the process of purchasing goods from suppliers, PT ABC also has problems, namely the recording of goods when purchasing goods is still recorded in the stock book and added with a calculator to find out the total stock of goods. The purpose of the research conducted is to produce an inventory information system using extreme programming methods that are useful to help solve problems that exist in inventory. The implementation of the extreme programming method in PT ABC inventory information system that occurs is displayed in the form of a report so that leaders can quickly find out the total number of incoming goods, outgoing goods, and inventory of goods that occur in the company.